Immobilization of Saccharomyces cerevisiae on Apple Pieces to Produce Cider - Clelia Altieri; Daniela Campaniello; Barbara Speranza; Milena Sinigaglia; Maria Rosaria Corbo; Antonio Bevilacqua (Fermentation, 2019)
Three yeasts (Saccharomyces cerevisiae var. boulardii, a commercial probiotic yeast; S. cerevisiae W13, a wild yeast able to remove ochratoxin A; and S. cerevisiae 17, a wild yeast with promising probiotic traits) were screened for their ability to adhere on apple pieces as a function of different contact times (15−30 min). Then, apple pieces were stored at 4 °C for 15 days, and the viable count of yeasts was periodically assessed. Yeasts were able to adhere on apple pieces after 15 min (7 log cfu/g) and retained their viability throughout the refrigerated storage. In a second step, apple pieces with S. cerevisiae W13 were used to produce cider on a small scale. The variables under investigation were (a) the recycling of pieces up to 10 times and (b) the preliminary storage of pieces at 4 °C before use. Pieces used immediately after yeast immobilization could be successfully used again 10 times and gained a fermentation performance (in terms of yeast amount in cider and ethanol after 24 h) similar to that achieved by free cells. In addition, the preliminary storage of pieces at 4 °C did not affect their performances as reusable starter carriers.